On the Approximation by Stancu-Type Bivariate Jakimovski–Leviatan–Durrmeyer Operators - Karateke, Seda; Zontul, Metin; Mishra, Vishnu Narayan; Gairola, Asha Ram (La matematica, 2024)
This paper deals with bivariate Stancu-type generalization of Jakimovski–Leviatan–Durrmeyer (JLD) operators in the approximation theory. Korovkin-type approximation properties of modified operators are also examined. Rate of convergence of these operators are investigated by means of the full and partial modulus of continuity. Further, weighted approximation properties of these operators are established. Some numerical applications will be also given to show the efficiency of this method.